Fracking : a reference handbook - Newton, David E. (Santa Barbara, California : ABC-CLIO, 2015)
Overview: The use of fracking is a tremendously important technology for the recovery of oil and gas, but the advantages and costs of fracking remain controversial. This book examines the issues and social, economic, political, and legal aspects of fracking in the United States. Provides readers with a complete historical review of the origins, development, and expansion of the use of fracking. -- Explains the technical principles related to the use of fracking in clear, nontechnical language. -- Presents an unbiased review of the arguments for and against the use of fracking for the recovery of oil and gas. -- Supplies a summary of the history of the use of fracking in the United States.
Preface -- Background And History: -- Genesis of fossil fuels -- Oil And Gas Resources: -- Terminology -- Exploring for oil and gas -- Drilling technology -- Petroleum chemistry -- Brief history of petroleum exploration -- Petroleum century -- Natural gas century -- Hydraulic Fracturing: -- History of hydraulic fracturing -- Horizontal drilling -- Conclusion -- References -- Problems, Controversies, And Solutions: -- Peak Oil And Gas: Still A Looming Threat Or Only A Distant Fantasy?: -- Global state of affairs -- Energy independence for the United States -- Benefits Of Fracking: -- Direct economic benefits -- Indirect economic benefits -- Environmental benefits -- Opposition to fracking -- Problems Associated With Hydraulic Fracturing: -- Water use -- Water contamination -- Air pollution -- Earthquakes -- Aesthetic and related disturbances -- Laws and regulations -- Conclusion -- References -- Perspectives: -- Introduction -- Separating fact from hype / Trudy E Bell -- Why fracking is beneficial / Bruce Everett -- Urgent need for global definition of terms in the reporting on fracking and seismic activity / Gina Hagler -- Fracking and the future of fresh water / Michael Pastorkovich -- Fracking by the numbers / John Rumpler -- Exploring alternative uses for fracking water / Lana Straub -- Fracking like it's your job: why worker safety in the fracking industry is so important / Laura Walter -- Feeding The Fracking Workforce: How Worker Nutrition Supports Health, Safety And Productivity / Christopher Wanjek -- Food as protection -- What workers need, and what workers get -- Return on investment -- References -- Profiles: -- Introduction -- American Gas Association -- American Petroleum Institute -- America's Natural Gas Alliance -- Chesapeake Climate Action Network -- Consumer Energy Alliance -- H John Eastman (1905-1985) -- Terry Engelder -- Environment America -- Food & Water Watch -- Ground Water Protection Council -- Erle P Halliburton (1892-1957) -- William Hart (1797-1865) -- Independent Petroleum Association of America -- Anthony R. Ingraffea (1947- ) -- International Energy Agency -- Interstate Natural Gas Association of America -- Interstate Oil and Gas Compact Commission -- EW Marland (1874-1941) -- Aubrey McClendon (1959- ) -- George Mitchell (1919-2013) -- National Association of Royalty Owners -- No Fracked Gas in Mass -- Edward AL Roberts (1829-1881) -- Endocrine Disruption Exchange -- Tom L Ward (1959- ) -- Waterkeeper Alliance -- Data And Documents: -- Introduction -- Data: Chemicals present in 652 different products used by hydraulic fracturing companies -- Discovered but unproved technically recoverable shale gas and oil resources in the United States: shale oil resources -- Estimated number of fracking wells in the United States -- Water used for fracking -- Estimated air pollution produced from early stages of fracking (drilling and well completion) in 2012 (tons) -- Estimated risked shale gas and shale oil resources in-place and technically recoverable in 41 countries as assessed in 2013 -- US crude oil and natural gas proved reserves -- Documents: -- Crude Oil Windfall Profit Tax Act of 1980 -- Hydraulic Fracturing Exclusions: -- Safe Drinking Water Act, Public law 113-103, Section 300h(d)(1) -- Clean Water Act, Public law 95-217, Sections 1326, 1342 -- Resource Conservation and Recovery Act (RCRA), Public law 94-580, 6921(b) -- Comprehensive Environmental Response, Compensation, and Liability Act (CERCLA-- also known as the Superfund Act), Public law 96-510, 9601 -- Legal Environmental Assistance Foundation versus US EPA, 118 F.3d 1467 (1977) -- Evaluation of Impacts to Underground Sources of Drinking Water by Hydraulic Fracturing of Coalbed Methane Reservoirs Study (2004) -- ES-8 Did EPA find any cases of contaminated drinking water wells caused by hydraulic fracturing in CBM wells? -- Testimony submitted to the House Committee on Natural Resources Subcommittee on Energy and Mineral Resources Washington, DC, June 18, 2009, prepared by the Interstate Oil and Gas Compact Commission on behalf of the nation's oil and gas producing states -- Study of the potential impacts of hydraulic fracturing on drinking water resources, progress report (2012) -- Act 13, State of Pennsylvania (2012) -- Robinson Township, et al versus Commonwealth of Pennsylvania, (J-127A-D-2012) (2013) -- Fracturing responsibility and Awareness of Chemicals Act S-1135, 113th Congress, 1st Session (2013) -- Powder River Basin Resource Council, Wyoming Outdoor Council, Earthworks, and Center for Effective Government (formerly OMB Watch) versus Wyoming Oil and Gas Conservation Commission and Halliburton Energy Services, Inc, 2014 WY 37 (2014) -- Norse Energy Crop. versus Town of Dryden, et al (2014) -- Communication from the Commission to the European Parliament, the Council, the European Economic and Social Committee and the Committee of the Regions on the Exploration and Production of Hydrocarbons (such as shale gas) using high volume hydraulic fracturing in the EU (2014) -- Resources For Further Research: -- Introduction -- Books -- Articles -- Reports -- Internet -- Chronology -- Glossary -- Index -- About the author.by the numbers / John Rumpler -- Exploring alternative uses for fracking water / Lana Straub -- Fracking like it's your job: why worker safety in the fracking industry is so important / Laura Walter -- Feeding The Fracking Workforce: How Worker Nutrition Supports Health, Safety And Productivity / Christopher Wanjek -- Food as protection -- What workers need, and what workers get -- Return on investment -- References -- Profiles: -- Introduction -- American Gas Association -- American Petroleum Institute -- America's Natural Gas Alliance -- Chesapeake Climate Action Network -- Consumer Energy Alliance -- H John Eastman (1905-1985) -- Terry Engelder -- Environment America -- Food & Water Watch -- Ground Water Protection Council -- Erle P Halliburton (1892-1957) -- William Hart (1797-1865) -- Independent Petroleum Association of America -- Anthony R. Ingraffea (1947- ) -- International Energy Agency -- Interstate Natural Gas Association of America -- Interstate Oil and Gas Compact Commission -- EW Marland (1874-1941) -- Aubrey McClendon (1959- ) -- George Mitchell (1919-2013) -- National Association of Royalty Owners -- No Fracked Gas in Mass -- Edward AL Roberts (1829-1881) -- Endocrine Disruption Exchange -- Tom L Ward (1959- ) -- Waterkeeper Alliance -- Data And Documents: -- Introduction -- Data: Chemicals present in 652 different products used by hydraulic fracturing companies -- Discovered but unproved technically recoverable shale gas and oil resources in the United States: shale oil resources -- Estimated number of fracking wells in the United States -- Water used for fracking -- Estimated air pollution produced from early stages of fracking (drilling and well completion) in 2012 (tons) -- Estimated risked shale gas and shale oil resources in-place and technically recoverable in 41 countries as assessed in 2013 -- US crude oil and natural gas proved reserves -- Documents: -- Crude Oil Windfall Profit Tax Act of 1980 -- Hydraulic Fracturing Exclusions: -- Safe Drinking Water Act, Public law 113-103, Section 300h(d)(1) -- Clean Water Act, Public law 95-217, Sections 1326, 1342 -- Resource Conservation and Recovery Act (RCRA), Public law 94-580, 6921(b) -- Comprehensive Environmental Response, Compensation, and Liability Act (CERCLA-- also known as the Superfund Act), Public law 96-510, 9601 -- Legal Environmental Assistance Foundation versus US EPA, 118 F.3d 1467 (1977) -- Evaluation of Impacts to Underground Sources of Drinking Water by Hydraulic Fracturing of Coalbed Methane Reservoirs Study (2004) -- ES-8 Did EPA find any cases of contaminated drinking water wells caused by hydraulic fracturing in CBM wells? -- Testimony submitted to the House Committee on Natural Resources Subcommittee on Energy and Mineral Resources
Includes bibliographical references and index.
Keywords: Hydraulic fracturing -- Environmental aspects; Gas well drilling -- Environmental aspects; Hydraulic fracturing -- Government policy -- United States